Copyright Protection for Digital Painting Commercialized by Brands without Artist Permission - Hadi, Zakia Tabita; Suherman, Suherman (Universitas Islam Sultan Agung, 2024)
The continuous development of digital art has tremendous impacts and also presents challenges for creators. The most frequent problem is art plagiarism. Easy internet access has made it easier for strangers to copy or even steal art for their own gain, leading to rights violations for the creator. This challenges the concepts of copyright and cyberspace, merging these two concepts into one concept, which is digital copyright. This paper compared digital copyright protection in Indonesia to that of the Digital Millennium Copyright Act of 1998 (DMCA) using a descriptive-analytical methodology. A normative jurisprudence approach was utilized in conjunction with secondary data for the study. According to the study's findings, digital copyright protection continues to prioritize physical objects over digital ones.